1994
DOI: 10.1001/archinte.154.16.1805
|View full text |Cite
|
Sign up to set email alerts
|

Diet and breast cancer risk. Results from a population-based, case-control study in Sweden

Abstract: As in most other studies, no strong risk factors for breast cancer have been identified in the current diet. The negative association between breast cancer risk and beta-carotene intake may be supported by a plausible mechanism, but our finding concerning alcohol should be interpreted cautiously since there was no dose-response relationship and the biological mechanism for a threshold effect at very low levels of consumption is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Of ten case-control studies, seven (Graham et al, 1991;Lee et al, 1991;London et al, 1992;Holmberg et al, 1994;Yuan et al, 1995;Freudenheim et al, 1996;Negri et al, 1996) suggest an inverse association with vitamin E intake and three (Toniolo et al, 1989;Gerber et al, 1990;Richardson et al, 1991) report null or positive associations; the results are statistically significant in four (Graham et al, 1991;London et al, 1992;Freudenheim et al, 1996;Negri et al, 1996) of the studies reporting inverse associations. The results from cohort studies are decidedly weaker: of five studies (Graham et al, 1992;Hunter et al, 1993;Rohan et al, 1993;Kushi et al, 1996;Verhoeven et al, 1997), only one (Graham et al, 1992) reports a relative risk of less than 0.90, and this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of ten case-control studies, seven (Graham et al, 1991;Lee et al, 1991;London et al, 1992;Holmberg et al, 1994;Yuan et al, 1995;Freudenheim et al, 1996;Negri et al, 1996) suggest an inverse association with vitamin E intake and three (Toniolo et al, 1989;Gerber et al, 1990;Richardson et al, 1991) report null or positive associations; the results are statistically significant in four (Graham et al, 1991;London et al, 1992;Freudenheim et al, 1996;Negri et al, 1996) of the studies reporting inverse associations. The results from cohort studies are decidedly weaker: of five studies (Graham et al, 1992;Hunter et al, 1993;Rohan et al, 1993;Kushi et al, 1996;Verhoeven et al, 1997), only one (Graham et al, 1992) reports a relative risk of less than 0.90, and this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Of 18 case-control studies, 14 (LaVecchia et al, 1987;Katsouyanni et al, 1988;Rohan et al, 1988;Iscovich et al, 1989;van 't Veer et al, 1990;Graham et al, 1991;Ingram et al, 1991;Lee et al, 1991;Zaridze et al, 1991;London et al, 1992;Levi et al, 1993;Holmberg et al, 1994;Freudenheim et al, 1996;Negri et al, 1996) observed a reduced risk of breast cancer among those in the highest category of carotenoid intake, whereas four (Marubini et al, 1988;Toniolo et al, 1989;Ewertz and Gill, 1990;Richardson et al, 1991) observed no reduction in risk. Of the inverse associations, six (Graham et al, 1991;Lee et al, 1991;Zaridze et al, 1991;Holmberg et al, 1994;Freudenheim et al, 1996;Negri et al, 1996) were statistically significant. A combined analysis of the data from eight case-control studies reported an odds ratio of 0.85 (P = 0.007) for the highest versus the lowest quintile of carotenoid intake (Howe et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21). For the 12 evaluated case-control studies (9,(159)(160)(161)(162)(163)(164)(165)(166)(167)(168)(169), the mean relative risk for high versus low fruit consumption was 0.66 and the range was 0.09-1.40 (Fig. 22).…”
Section: Breastmentioning
confidence: 99%
“…A lower threshold value (15 g alcohol day In both of these studies, the relative risk was under 2. On the other hand, no association between alcohol and the risk of breast cancer was found in the New York State Cohort 5,23 and in the Sweden Mammography Cohort 5,24 . It also seems that the strength of the association between alcohol and breast cancer risk decreases with an increase in follow-up time 1 .…”
Section: Discussionmentioning
confidence: 86%